Improving the Quality of Rabbit Manure in Livestock Farming Groups in The Bedugul Tourist Area, Tabanan-Bali - Anak Agung Ngurah Mayun Wirajaya Wirajaya; Made Sri Yuliartini; I Gusti Agus Maha Putra Sanjaya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
To support the growth and development of plants in the Bedugul tourist area, in addition to using inorganic fertilizers, most farmers still use organic fertilizer derived from chicken manure which is easily obtained in large quantities from outside the Candikuning Village area. Only now, the source of organic fertilizer that can be used from solid and liquid rabbit manure in Candikuning Village still needs to be carried out further processing to improve the quality of rabbit manure as a nutrient source fertilizer for plants. Livestock farmer groups can use this opportunity in Candikuning Village to supply organic fertilizer from solid and liquid rabbit manure. The group's problem is that solid and liquid rabbit manure has not been processed optimally, there is no house where the drying and fermentation process has not been carried out, and packaging and labeling have not been carried out. Therefore, partner groups need to be facilitated by processing technology and improving the quality of rabbit waste, packaging and labeling, product quality testing in the laboratory, and partner group business management. This Community service program is carried out in livestock farming groups in Candikuning Village, Baturiti District, Tabanan Regency-Bali Province. The method used to achieve the goal is through socialization, counseling, mentoring, training, and applying technology with direct practice in the field. In this activity, the output target that has been achieved is that the partner group is independently able to utilize solid and liquid rabbit manure waste into